Konseling Pranikah bagi Generasi Z - Nor Mita Ika Saputri; Vitria Larseman Dela; Sukatno; Khairul Amri; Pikarani (PAKAT: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service program aimed to address the unique premarital challenges faced by Generation Z (aged 18–24) in Indonesia by providing an interactive premarital counseling talk show. The initiative responded to key issues including low literacy on healthy marriage foundations, misconceptions about marriage preparation, limited access to professional counseling, and deficits in interpersonal communication skills. The method employed a participatory hybrid approach combining offline seminars, role-play conflict simulations, documentary screenings, and expert-led group counseling. The program reached 200 participants, consisting of students, young workers, and entrepreneurs. Results indicated significant improvements in knowledge across key areas, especially relational psychology (from 42% to 87%) and marriage law (from 31% to 68%). Most participants (89%) successfully applied active listening techniques. Supporting factors included peer-led discussions, contextual materials, and gamified assessments. Challenges such as low male participation and technical limitations in rural areas were mitigated through gender-specific modules and print-based learning. The program proved effective in enhancing Generation Z's readiness for marriage through inclusive, co-designed, and sustainable educational strategies.